Wizerunek uczelni wyższej w świetle opinii studentów (na przykładzie Akademii Ekonomicznej we Wrocławiu) - Mazurek-Łopacińska, Krystyna (The Image of a School of Higher Education on the Example of the Wrocław University of Economics. Student's Opinion, 2008)
Selected research outcomes presented in the article show student's opinion on various features of the Wrocław University of Economics. Their opinion was analyzed concentrating on the reasons why somebody choose this particular college. The most important university ranking criteria were: university prestige, education offer, university atmosphere, relations with the environment, public relations actions and university infrastructure, Besides these aspects of image, emotional attachment to the university as well as behavioral aspects expressed through the recommendation disposition of the school to members of the datum group (for example friends or family). Moreover, willingness to make the same school choice was also examined. These conclusion were created in the order to designate the direction of the changes in school offer which are important in shaping image.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 33, s. 9-26